2021
DOI: 10.1038/s41598-021-89128-0
|View full text |Cite
|
Sign up to set email alerts
|

Bortezomib induces methylation changes in neuroblastoma cells that appear to play a significant role in resistance development to this compound

Abstract: The anticancer activity of bortezomib (BTZ) has been increasingly studied in a number of indications and promising results for the use of this treatment have been shown in neuroblastoma. As BTZ treatment is usually administered in cycles, the development of resistance and side effects in patients undergoing therapy with BTZ remains a major challenge for the clinical usage of this compound. Common resistance development also means that certain cells are able to survive BTZ treatment and bypass molecular mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 54 publications
0
16
0
Order By: Relevance
“…Epigenetic changes that arise because of the action of BTZ cause global changes in the functioning of cells. As we showed in our previous study [ 27 ], treatment of SH-SY5Y tumor cells with a single dose of BTZ caused a complete change in the DNA methylation profile, which is probably responsible for the development of resistance to BTZ. This proves the multidirectional activity of BTZ and its influence on the dysregulation of thousands of genes and miRNA molecules, disrupting many signaling pathways and biological processes.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Epigenetic changes that arise because of the action of BTZ cause global changes in the functioning of cells. As we showed in our previous study [ 27 ], treatment of SH-SY5Y tumor cells with a single dose of BTZ caused a complete change in the DNA methylation profile, which is probably responsible for the development of resistance to BTZ. This proves the multidirectional activity of BTZ and its influence on the dysregulation of thousands of genes and miRNA molecules, disrupting many signaling pathways and biological processes.…”
Section: Discussionmentioning
confidence: 64%
“…BTZ is able to initiate epigenetic changes by altering the level of global DNA methylation in MM patients [ 24 ] and is involved in the regulation of miRNAs’ levels [ 14 , 25 , 26 ]. In our previous studies [ 27 ], we have shown significant epigenetic changes, manifested by a complete change in the DNA methylation profile, induced by the action of BTZ on cancer neuroblastoma cells. We have also observed that DNA methylation changes transferred to daughter cells are possibly involved in the development of resistance to BTZ.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently published a study describing a key role of BTZ-induced methylation changes in the development of resistance to BTZ of the SH-SY5Y neuroblastoma cell line, subjected to treatment with this compound [ 13 ]. To investigate whether methylation changes induced by BTZ in dLUHMES cells are specific to these cells, we analyzed the methylation level of a subset of CpG sites that we identified to be affected by BTZ exposure, using the data from our previous study.…”
Section: Resultsmentioning
confidence: 99%
“…To assess the specificity of identified methylation changes, we compared the methylation levels at the CpG sites that exhibited methylation changes after BTZ treatment in dLUHMES cells with the methylation levels observed in SH-SY5Y cells, used in our previous analysis of the influence of BTZ treatment on cell methylomes [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation